Myeloid-associated differentiation marker is a novel SP-A-associated transmembrane protein whose expression on airway epithelial cells correlates with asthma severity - Dy, Alane Blythe C.; Langlais, Paul R.; Barker, Natalie K.; Addison, Kenneth J.; Tanyaratsrisakul, Sasipa; Boitano, Scott; Christenson, Stephanie A.; Kraft, Monica; Meyers, Deborah; Bleecker, Eugene R.; Li, Xingnan; Ledford, Julie G. (Scientific reports, 2021)
Surfactant protein A (SP-A) is well-known for its protective role in pulmonary immunity. Previous studies from our group have shown that SP-A mediates eosinophil activities, including degranulation and apoptosis. In order to identify potential binding partners on eosinophils for SP-A, eosinophil lysates were subjected to SP-A pull-down and tandem mass spectrometry (MS/MS) analysis. We identified one membrane-bound protein, myeloid-associated differentiation marker (MYADM), as a candidate SP-A binding partner. Blocking MYADM on mouse and human eosinophils ex vivo prevented SP-A from inducing apoptosis; blocking MYADM in vivo led to increased persistence of eosinophilia and airway hyper-responsiveness in an ovalbumin (OVA) allergy model and increased airways resistance and mucus production in a house dust mite (HDM) asthma model. Examination of a subset of participants in the Severe Asthma Research Program (SARP) cohort revealed a significant association between epithelial expression of MYADM in asthma patients and parameters of airway inflammation, including: peripheral blood eosinophilia, exhaled nitric oxide (FeNO) and the number of exacerbations in the past 12 months. Taken together, our studies provide the first evidence of MYADM as a novel SP-A-associated protein that is necessary for SP-A to induce eosinophil apoptosis and we bring to light the potential importance of this previously unrecognized transmembrane protein in patients with asthma.